Immunopathological aspects of oral erythema multiforme - Maharani Laillyza Apriasari; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Erythema multiforme is an acute disease on the skin and mucous membrane. This lesion can erupt in mucous membranes of the oral cavity. Improper and late treatment may cause Stevens Johnson syndrome which may cause patient mortality, therefore proper and accurate diagnosis are needed. Purpose: The immunopathological aspect of oral erythema multiforme through literature study can help us to find the definite diagnosis and to know the differential diagnosis. review: In immunopathology, minor type of erythema multiforme is vasculitis caused by the immune complex hypersensitivity reaction among antigen antibodies. The mayor type of erythema multiforme may appeared from autoimmune reaction and from untreated minor type of erythema multiforme. Conclusion: Immunopathological approach of erythema multiforme is important beside the clinical manifestation, histology, and the differential diagnosis to find the definitive diagnosis.